Atlas of skin cancers practical guide to diagnosis and treatment - Hendi, Ali (Springer, 2011)
The incidence of skin cancer has risen rapidly in recent decades, and patients often present initially to practitioners in many different specialties. Because skin cancer can vary in clinical appearance, even dermatologists may experience difficulty in reaching a clinical diagnosis. For primary care physicians and physician extenders (physician assistants, nurses, and nurse practitioners), who have had very little or no formal training in dermatology, the task can be still more daunting. In this atlas, the authors set out to provide a practical resource that will help improve the 'visual vocab.